STRUCTURE ELUCIDATION OF ALKALOIDS FROM LEAVES OF Voacanga foetida (Bl.) Rolfe OF LOMBOK ISLAND - Surya Hadi; Dina Asnawati; Novi Febrianti (Universitas Gadjah Mada, 2010)
The leaves of Voacanga foetida (Bl.) Rolfe, have been used ethnomedically for the treatment of wounds, itches, and swellings particularly in Lombok island. A phytochemical study has been done to investigate chemical compounds responsible against the cause of the diseases. By separating alkaloidal fraction from the leaves was found voacristine 1 as the major alkaloidal compound, and voacangine 2 and coronaridine 3 as the minor components. The structure elucidation of the compounds was carried out on the basis of spectroscopy data. A structure revision of voacristine 1 was also reported.